Penguatan Literasi Digital Pada Remaja Berbasis Masjid - Virga, Rika Lusri; Astuti, Yanti Dwi (MENARA RIAU, 2024)
Teenage mosques are still unable to maximize their role in society amid the onslaught of various information from the media which is rife with miss-information and dis-information. this phenomenon requires the participation of mosque-based youth is needed to maintain the character of the nation's generation in social media (social media). It is time for mosque youth to take part in the form of community service to further see the real reality. Because of the dramatic reality at this time the existence of the mosque only used for worshiping the God. This research uses Community Based Research (CBR) methods starting from Laying the Foundation, Planning, Information Gathering and Acting on Finding. The theory used as a knife of analysis is basic literacy, digital literacy to the concept of ten digital literacy. The results of the study showed that mosque youths already possessed several digital literacy competencies, however, they were still unable to fulfill production and collaboration competencies when carrying out their functions as mosque youth in a heterogeneous society with levels of education, age, ethnicity and religion. For this reason, a movement is needed related to digital literacy counseling to mosque youth so that they can be the driving force of digital literacy in society.